Physically Triggered Morphology Changes in a Novel Acremonium Isolate Cultivated in Precisely Engineered Microfabricated Environments - Catón, Laura; Yurkov, Andrey; Giesbers, Marcel; Dijksterhuis, Jan; Ingham, Colin J. (Frontiers in Microbiology, 2017)
Fungi are strongly affected by their physical environment. Microfabrication offers the possibility of creating new culture environments and ecosystems with defined characteristics. Here we report the isolation of a novel member of the fungal genus Acremonium using a microengineered cultivation chip. This isolate was unusual in that it organizes into macroscopic structures when initially cultivated within microwells with a porous aluminum oxide (PAO) base. These “templated mycelial bundles” (TMB) were formed from masses of parallel hyphae with side branching suppressed. TMB were highly hydrated, facilitating the passive movement of solutes along the bundle. By using a range of culture chips, it was deduced that the critical factors in triggering the TMB were growth in microwells from 50 to 300 µm in diameter with a PAO base. Cultivation experiments, using spores and pigments as tracking agents, indicate that bulk growth of the TMB occurs at the base. TMB morphology is highly coherent and is maintained after growing out of the microwells. TMB can explore their environment by developing unbundled lateral hyphae; TMB only followed if nutrients were available. Because of the ease of fabricating numerous microstructures, we suggest this is a productive approach for exploring morphology and growth in multicellular microorganisms and microbial communities.